The Ex-Ante Evaluation of Hotel Buildings Height in Airport Area: A Case of Hotel in Kaliwungu, Peri-Urban Area of Semarang - Anang Wahyu Sejati; Sri Rahayu; Bitta Pigawati; Jurike Winarendri (Journal of Architectural Design and Urbanism, 2018)
This paper conveys the findings on hotel buildings evaluation in the peri-urban of Semarang based on ex-ante evaluation. Ex-ante is an evaluation model before project activities are implemented to minimize development impacts. Evaluation of altitude was done with three models, namely the ratio of floor area (FAR), Angle of Light Obstruction (ALO), and building height calculation in the airport area applicable in Indonesia. Furthermore, the evaluation of the strategic value of the location with three criteria was the proximity of industrial zone, accessibility, and proximity to tourist destinations. This study was successfully answers the question of maximal height rules and the number of stories allowed for hotel buildings in peri-urban Semarang. The result suggest the regulation of building height in Kaliwungu especially for hotel building in aviation safety area. Maximum height allowed is 32.5 m or 8 stories. The existing regulations have not regulated these issues, so collaborative planning should be carried out between the government of Semarang City and Kendal Regency. With collaborative planning, problems in both regions, especially regarding the height of buildings such as hotels can be coordinated.